Exploring the neural mechanisms of electroacupuncture for cognitive impairment in depression using functional near-infrared spectroscopy: a randomized controlled trial - Yuan, Jie; Qi, Rongrong; Zhang, Yuting; Ma, Xinghua; Zhao, Tian; Sun, Ying; Yang, Tingting; Lei, Yaling (Frontiers in Psychiatry, 2025)
BackgroundDepression is a prevalent psychiatric disorder that is commonly associated with a high risk of recurrence and suicide. One of its core symptoms is cognitive impairment, which can occur during the prodromal, acute (76.9 – 94.0%), and remission phases (32.4 – 44.0%). This impairment substantially contributes to both health and socioeconomic burdens. Recent evidence suggests the therapeutic potential of electroacupuncture; however, its adjunctive efficacy compared with that of standard pharmacotherapy remains ambiguous. This study aimed to assess the effectiveness and safety of using conventional antidepressants alone versus in combination with electroacupuncture.MethodsThis multicenter, prospective, open-label randomized controlled trial enrolled 120 patients diagnosed with depression. The patients were randomly assigned at a 1:1 ratio to receive either conventional pharmacotherapy alone or pharmacotherapy combined with electroacupuncture. The intervention lasted for four weeks, followed by a post-treatment observation period. The Perceived Deficits Questionnaire for Depression (PDQ-D) was the primary outcome measured. The 17-item Hamilton Depression Rating Scale (HAMD-17), N-back task, Stroop Color-Word Test (SCWT), Trail Making Test-Part B (TMT-B), and functional near-infrared spectroscopy (fNIRS) indicators, such as the concentration of oxyhemoglobin (oxy-Hb), integral values, and centroid values, were the secondary outcomes assessed. R 4.5.0 was used to conduct the analyses.ResultsA total of 103 of the 120 participants completed the study. Significant main effects of time and time ×group interactions across most outcomes (P < 0.05) were revealed using linear mixed-effects modeling. The electroacupuncture group demonstrated significantly lower PDQ-D scores (P < 0.05) post-treatment, indicating greater cognitive improvement. This group also demonstrated superior performance in HAMD-17, N-back, SCWT, TMT-B, and fNIRS metrics. Most group main effects were non-significant (P > 0.05); however, the interaction effects indicated a stronger response to the combined intervention.ConclusionCompared with pharmacotherapy alone, the combination of pharmacotherapy with electroacupuncture improved cognitive symptoms, mood, and executive function more effectively in patients with depression over a short period. In addition, this combination was associated with enhanced cortical activation on fNIRS. The combined treatment was found to be safe and effective, suggesting promising implications for clinical practice and future research.Clinical trial registrationhttps://www.chictr.org.cn/hvshowproject.html?id=250167&v=1.0, identifier ChiCTR2400082987